Occurrence of Diplostomum spp. (Diplostomum) in some fish species from Ömerli Dam Lake, Istanbul, Turkey - (:unkn) unknown (FRS Marine Laboratory, 2014)
Occurrence and infection dynamics of Diplostomum spp. in the lens of the eyes of bleak Alburnus istanbulensis, Prussian carp Carassius gibelio, chub Squalius cephalus, rudd Scardinius erythrophthalmus and vimba bream Vimba vimba were studied at monthly intervals. The study was performed between May 2012 and January 2013. In total; 17 A. istanbulensis, 88 C. gibelio, 62 S. cephalus, 19 S. erythrophthalmus and 71 V. vimba specimens were examined. The overall parasite prevalence and mean intensity (MI) respectively for the fish species were; A. istanbulensis, 82.4%, 6.8(MI), C. gibelio 43.2%, 3.4(MI), S. cephalus 62.9%, 6.4(MI), S. erythrophthalmus 15.8%, l.O(MI) and V. vimba 97.2%, 45.8(MI). The results show that highest prevalence and mean intensity of infection was recorded in V. vimba. Conversely, S. erythrophthalmus has lowest infection rates. Generally, prevalence of the infection was found higher during late summer and early fall.